Enhancing Students’ Science Process Skills through Local Wisdom Based Biology Worksheets in Ecology and Biodiversity Learning - Anjelia, Bella; Hastiana, Yetty; Astrid S.W. Sumah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
The low relevance of biology subject matter to the local context has resulted in students having limited in-depth understanding of concepts. This research focuses on evaluating the implementation of a Student Worksheet rooted in local wisdom in biology learning, specifically on ecology and biodiversity, through the guided inquiry model. The research employed a descriptive approach at the worksheet implementation stage with seventh-grade students as subjects. Data were obtained from the N-gain score of a written test on. Research data were derived from the N-gain score of a written test on SPS and from the evaluation of worksheet implementation over four meetings. The findings show an N-gain score of 0.51, classified into medium, indicating that the worksheet rooted in local wisdom was able to enhance students’ SPS, foster active engagement, and facilitate concept comprehension. The evaluation results revealed that almost all biology learning activities were implemented, and reflections showed positive responses as the material was relevant to daily life.The worksheet based on local wisdom is feasible to be used as an alternative biology teaching material employing the guided inquiry model at MTs Nurul Ula Desa Burai.